2010
DOI: 10.1007/s10637-010-9616-y
|View full text |Cite
|
Sign up to set email alerts
|

Anoikis induction and metastasis suppression by a new integrin αvβ3 inhibitor in human melanoma cell line M21

Abstract: Integrin αvβ3 plays a critical role in the survival and metastasis process of cancer cells. It is therefore desirable to develop new types of small molecule inhibitors of integrin αvβ3. IH1062 (3, 5-dichloro-phenylbiguanide) is a novel small molecule inhibitor of integrin αvβ3 that we have recently discovered. In this study, we investigated the induction effects of anoikis in human melanoma cell line M21 by IH1062, by detecting caspase activity, measuring the expression levels of apoptosis-related proteins, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 14 publications
1
11
0
Order By: Relevance
“…Detached cells form cell clusters in the culture supernatant. These tumor cells, however, are resistant to anoikis and can survive for some time [46][48]. After enzyme removal, CD44 de novo synthesis reconstitutes its surface expression, and cell cycle resumes after tumor cell adhesion.…”
Section: Discussionmentioning
confidence: 99%
“…Detached cells form cell clusters in the culture supernatant. These tumor cells, however, are resistant to anoikis and can survive for some time [46][48]. After enzyme removal, CD44 de novo synthesis reconstitutes its surface expression, and cell cycle resumes after tumor cell adhesion.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown an association between Integrin signaling and apoptosis/ anoikis. 21,22 For example, Zhang et al 23 described that treatment of melanoma cells with an inhibitor of Integrin aVb3 promotes anoikis and activates caspase cascades. Hence, it is feasible that Dido1-dependent upregulation of Integrin aV in malignant melanoma results in an enhanced resistance to apoptosis.…”
Section: Dido1 Promotes Melanoma Progression S Braig and A-k Bosserhoffmentioning
confidence: 99%
“…In M21 (human melanoma cell line) it induced anoikis, lead to decrease of Bcl-2/Bax ratio and survivin proteins, dephosphorylate Tyr925 in the carboxyl region of FAK. It also inhibited the pulmonary metastases in established melanoma pulmonary metastasis mouse model in dose dependent manner [59]. These in vitro and in vivo results established for IH1062 in human melanoma cells is promising development to treat and prevent tumor metastasis.…”
Section: Integrin Antagonists In Tumor and Angiogenesis Inhibitionmentioning
confidence: 71%